Biocompatibility study of tobacco mosaic virus nanoparticles on human alveolar bone cells - Aunjida Chawanarojnarit; Nirada Dhanesuan; Jittima Amie Luckanagul; Sorasun Rungsiyanont (Elsevier, 2022)
One of the most important factors in a dental implant's success is an adequate quantity of supporting bone. However, there are still some limitations for the bone substitution material. Previous studies found that tobacco mosaic virus (TMV) had the potential for bone formation induction. The aim of this study was to evaluate the biocompatibility of TMV with primary human alveolar bone cells. Primary human alveolar bone cells were cultured on TMV coated substrates. Cell viability, alkaline phosphatase activity, calcium matrix mineralization forming ability, immunofluorescence staining for osteocalcin synthesis and cell morphology were assessed. The results showed that primary human alveolar bone cells cultured on the TMV coated substrates had a higher metabolic rate than the non-TMV coated control group at days 1, 3, 7 and 14. Moreover, the calcium deposition was positive and the alkaline phosphatase activity assay was found significantly greater than the control group at day 14 (p < 0.05). The osteocalcin protein synthesis was found in both the TMV coated substrates and the control group. The immunofluorescence study revealed that in the TMV coated substrates group, the cell morphology changed into a polygonal shape and aggregated more quickly than the control group. The present findings conclude that TMV is biocompatible with primary human alveolar bone cells and also shows osteoinduction potential.